2019
DOI: 10.1111/ssqu.12641
|View full text |Cite
|
Sign up to set email alerts
|

“Is There Anybody Out There?”: Communication of Natural Hazard Warnings at Home and Away

Abstract: Objective. This article examines various determinants of communication behaviors related to natural hazards and how those determinants vary for those at home or those away from home. We use the context of a series of storms that provoked communication to determine differences across media platforms, location during the event, sending versus receiving communication, and certain demographic characteristics. Methods. We use a survey of Oklahoma residents fielded in the Spring of 2016 following a series of storms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Research in emergency management has documented the important contingent effect of a large variety of demographic variables that are related to individual emergency preparedness. Previous studies have shown that age (Ablah et al, ; Heller, Alexander, Gatz, Knight, & Rose, ; Lindell & Perry, ), gender (Blessman et al, ; Eisenman et al, ; Murphy et al, ; Robinson, Pudlo, & Wehde, ), education (Fothergill & Peek, ; Russell, Goltz, & Bourque, ), income (Ablah et al, ; Edwards, ), location (Wehde, Pudlo, & Robinson, ), and race/ethnicity (Brodie, Weltzien, Altman, Blendon, & Benson, ; Eisenman et al, ; Peacock, Morrow, & Gladwin, ; Redlener et al, ; Torabi & Seo, ) capture important individual differences that structure individual emergency preparedness and response. Additionally, individuals who have children at their residences tend to be more prepared for disasters (Baker & Cormier, ; Edwards, ; Russell et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research in emergency management has documented the important contingent effect of a large variety of demographic variables that are related to individual emergency preparedness. Previous studies have shown that age (Ablah et al, ; Heller, Alexander, Gatz, Knight, & Rose, ; Lindell & Perry, ), gender (Blessman et al, ; Eisenman et al, ; Murphy et al, ; Robinson, Pudlo, & Wehde, ), education (Fothergill & Peek, ; Russell, Goltz, & Bourque, ), income (Ablah et al, ; Edwards, ), location (Wehde, Pudlo, & Robinson, ), and race/ethnicity (Brodie, Weltzien, Altman, Blendon, & Benson, ; Eisenman et al, ; Peacock, Morrow, & Gladwin, ; Redlener et al, ; Torabi & Seo, ) capture important individual differences that structure individual emergency preparedness and response. Additionally, individuals who have children at their residences tend to be more prepared for disasters (Baker & Cormier, ; Edwards, ; Russell et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, though it is true that U.S. media coverage reveals the racial makeup of the social and economic classes most damaged by critical events (Bobo, ; Falk, Hunt, and Hunt, ), and portrays disaster survivors in positive or negative lights according to race (Sommers et al., ), biases in the media are less likely to affect the political trust of disaster survivors than of disaster observers (Reinhardt , ). In the disaster context, education and knowledge are linked to both types of communication about the event (Wehde, Pudlo, and Robinson, ) and sustained public attention during the event (see Yeo and Knox, ). As such, education is no longer expected to exacerbate the difference in trust between black and white survivors.…”
Section: Political Trust and Disastersmentioning
confidence: 99%
“…These effects may move citizens further away from working within democratic political channels that facilitate peace (Hendrix & Salehyan, 2012). Disasters generate unique emotional contexts that alter the way people process information (Atkeson & Maestas, 2012; Canales, Pope & Maestas, 2019; Wehde, Pudlo & Robinson, 2019); this in turn changes how people attribute blame and evaluate policy proposals (Gomez & Wilson, 2008; Plein, 2019; Pope & Leland, 2019; Reinhardt & Ross, 2019); survivors attribute blame toward minorities and prefer restrictive policies against out-groups.…”
Section: Theoretical Foundationsmentioning
confidence: 99%